2021
DOI: 10.3233/nre-201525
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and sustained effects of a three-week neuro-developmental treatment intensive: A case series report

Abstract: BACKGROUND: Neuro-Developmental Treatment (NDT) currently embraces evidence-based concepts of motor control, motor learning and neuroplasticity. However, most research has been performed on outdated models of NDT. OBJECTIVE: This case series examines the short- and long-term outcomes of a three-week intensive using contemporary NDT interventions. METHODS: Six children, 2–10 years old with neurologic disorders and Gross Motor Function Classification System (GMFCS) levels I-III participated in the intervention. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…A case series published in 2021 reported that intensive NDT had positive results in six children with neurologic conditions. six children aged 2-10 years were included in this study and the outcome measure used was GMFM-66 [ 12 ]. In a 2015 study, Labaf et al found that NDT enhanced gross motor function in children with CP in four categories: lying and rolling, sitting, crawling and kneeling, and standing; 28 CP children were included in this study and the outcome measure used was GMFM [ 13 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A case series published in 2021 reported that intensive NDT had positive results in six children with neurologic conditions. six children aged 2-10 years were included in this study and the outcome measure used was GMFM-66 [ 12 ]. In a 2015 study, Labaf et al found that NDT enhanced gross motor function in children with CP in four categories: lying and rolling, sitting, crawling and kneeling, and standing; 28 CP children were included in this study and the outcome measure used was GMFM [ 13 ].…”
Section: Reviewmentioning
confidence: 99%
“…These areas of improvement are summarized in Table1. Gross motor[7,10,11,12,13,14,15,17,18,22,23,24,25,32,37,38,44,45,46,47,51,52,55,60] 2Balance[7,8,28,30,35,43,51,57] 3 Postural control/trunk control[7,8,27,28,35,57]…”
mentioning
confidence: 99%
“…Pemberian bobath juga dapat meningkatkan keseimbangan duduk pada anak cerebral palsy spastik diplegi dibandingkan dengan terapi pilates (Sari et al, 2016). Apabila ingin mendapatkan hasil yang lebih optimal, terapi bobath harus dilakukan secara intensif dan konsisten, terapi bobath yang dilakukan secara intensif (3-11 kali perminggu) dapat memberikan hasil yang lebih baik dibandingkan dengan terapi konvensional yang dilakukan 1-2 kali perminggu (Swiggum et al, 2021). Pemberian terapi yang konsisten dapat meningkatkan fungsi motorik kasar pada anak (Kalaichandran, Swarnakumari, 2019) dan meningkatkan aktivasi otot extensor trunk yang dapat dilihat melalui sinyal EMG (Grazziotin dos Santos et al, 2015).…”
Section: Hasil Dan Pembahasanunclassified